“One Out–All Out” Principle in the Water Framework Directive 2000—A New Approach with Fuzzy Method on an Example of Greek Lakes (2021)
Latinopoulos, D., M. Spiliotis, C. Ntislidou, I. Kagalou, D. Bobori, V. Tsiaoussi, and M. Lazaridou. 2021. “One Out–All Out” Principle in the Water Framework Directive 2000—A New Approach with Fuzzy Method on an Example of Greek Lakes. Water 2021, 13, 1776. https://doi.org/10.3390/w13131776